2002
DOI: 10.1159/000054731
|View full text |Cite
|
Sign up to set email alerts
|

The Product of Duration and Amount of Proteinuria (Proteinuria Index) Is a Possible Marker for Glomerular and Tubulointerstitial Damage in IgA Nephropathy

Abstract: Background/Aims: IgA nephropathy (IgAN) is one of the major causes for chronic renal failure (CRF). Presence of massive proteinuria, hypertension, increased serum creatinine level and sclerotic histopathological changes of the glomerulus are known to be determinants for the progression of CRF. However, the relationships between duration of proteinuria/hematuria and histopathological changes, which may be correlated with the renal prognosis, have not been clarified. Methods: A cross-sectional, univariate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The duration of abnormal urinalysis prior to biopsy was 4.7 years (range 0. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The mean Ccr was 84.4 ml/min/1.73 m 2 (range 24.3-156.9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of abnormal urinalysis prior to biopsy was 4.7 years (range 0. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The mean Ccr was 84.4 ml/min/1.73 m 2 (range 24.3-156.9).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, therefore, we wanted to investigate the relationship between vascular lesions and hypertension in renal parenchymal disease. To avoid unnecessary complexity of the histopathological findings, we chose IgAN, which is known as the most common primary glomerular disease in Japan (13), as a single disease entity of renal parenchymal disease. Moreover, although nephrologists tend to regard patients with hypertension and mild proteinuria as having benign nephrosclerosis, it is important to reveal whether this diagnosis is correct.…”
Section: Introductionmentioning
confidence: 99%
“…37 Several clinical studies have shown that proteinuria is a strong prognostic factor for IgAN progression. 8,9,12 Our study revealed multiple podocyte injuries in proteinuric IgAN, including decreased cell-cycle protein p27, decreased type IV intermediate filament nestin expression, widened foot process and ultimately decreased podocyte density. We further showed that podocyte injury, especially the number of podocytes is a better predictor of progression than the level of proteinuria at the time of biopsy in IgAN.…”
Section: Discussionmentioning
confidence: 70%
“…8 However, emerging studies have found that, rather than the amount of proteinuria appearing at diagnosis, it is the change in magnitude of the proteinuria that is a stronger predictor of renal outcome. 4,[8][9][10][11][12] Consistent with these findings, a recent study reported that patients who achieved a sustained reduction in proteinuria have a better prognosis regardless the initial proteinuria level. 13 Another study also showed that mean proteinuria during follow-up was a powerful independent prognostic predictor in IgAN.…”
mentioning
confidence: 66%
“…10 Proteinuria is an important and independent predictor of adverse outcomes in patients with glomerulopathies, including IgAN. 3,[11][12][13] While nephrotic range proteinuria levels are necessary to confirm a poor prognosis in most glomerular diseases, this seems to happen at much lower levels in primary IgAN. 3,11,12 The goal of any treatment of IgAN aims to decrease the proteinuria levels in order to provide a cure or at least achieve better long-term renal survival.…”
Section: Introductionmentioning
confidence: 99%